Dangerous liaisons: complement, coagulation, and kallikrein/kinin cross‐talk act as a linchpin in the events leading to thromboinflammation. Issue 1 (November 2016) - Ekdahl, Kristina N.; Teramura, Yuji; Hamad, Osama A.; Asif, Sana; Duehrkop, Claudia; Fromell, Karin; Gustafson, Elisabet; Hong, Jaan; Kozarcanin, Huda; Magnusson, Peetra U.; Huber‐Lang, Markus; Garred, Peter; et al.
Summary: Innate immunity is fundamental to our defense against microorganisms. Physiologically, the intravascular innate immune system acts as a purging system that identifies and removes foreign substances leading to thromboinflammatory responses, tissue remodeling, and repair. It is also a key contributor to the adverse effects observed in many diseases and therapies involving biomaterials and therapeutic cells/organs. The intravascular innate immune system consists of the cascade systems of the blood (the complement, contact, coagulation, and fibrinolytic systems), the blood cells (polymorphonuclear cells, monocytes, platelets), and the endothelial cell lining of the vessels. Activation of the intravascular innate immune system in vivo leads to thromboinflammation that can be activated by several of the system's pathways and that initiates repair after tissue damage and leads to adverse reactions in several disorders and treatment modalities. In this review, we summarize the current knowledge in the field and discuss the obstacles that exist in order to study the cross‐talk between the components of the intravascular innate immune system. These include the use of purified in vitro systems, animal models and various types of anticoagulants. In order to avoid some of these obstacles we have developed specialized human whole blood models that allow investigation of the cross‐talk between the various cascade systems and the blood cells. We in particular stress that platelets are involved in these interactions and that the lectin pathway of the complement system is an emerging part of innate immunity that interacts with the contact/coagulation system. Understanding the resulting thromboinflammation will allow development of new therapeutic modalities.